Sessile Drop Method Prediction of Particleboard Mechanical Properties - Mekro Permana Pinem; Aldiansyah Rudy Adiwinoto; Yusvardi Yusuf; Dhimas Satria; Dwianto Dwianto; Sunardi Sunardi; Hendra Hendra; Nufus Kanani; Harly Demustila; Dimas Triwibowo (Department of Mechanical Engineering, Universitas Andalas, 2024)
Agriculture waste-based materials have considerable potential as wood-based particleboard alternatives. It has been produced abundantly from nature and considers an eco-friendly material. One of the enormous resources is the paddy by-product, rice straw (about 500 million tonnes per year worldwide). In this work, the mechanical properties of rice straw-based particleboard are predicted easily and quickly using the sessile drop method. Rice straw was crushed into 2-5 mm diameter powder-like materials, and corn starch was used as the binder. The rice straw particleboard was formed under a hot press machine (5 MPa, 180°C and 120 minutes). Conventionally, the sample mechanical property was tested through Universal Testing Machine (UTM). Unfortunately, the process is costly and difficult to access. It is necessary to have a rapid and low-cost presumption of the mechanical particleboard properties toward more efficient manufacturing. This work proposes a simple sessile drop method to indicate particleboard mechanical properties. Multiple linear regression was performed to see the correlation between sessile drop and UTM testing. It was found statistically that the sessile drop method could be used as an early prediction of particleboard mechanical properties.